The transformation of personalisation in hospitality through the implementation of artificial intelligence (AI) - Khushboo Bilal; Sajad Ahmad Bhat; Danish Iqbal Raina; Parvez Abdulla; Zakir Hussain; Nur Azizah (Borneo Novelty Publishing, 2025)
Purpose – This paper aims to explore the significant impact of Artificial Intelligence (AI) on personalizing guest experiences within the hospitality industry. It investigates how AI-driven solutions are revolutionizing the customization of services and improving operational efficiency.Methodology/Design/Approach - The study uses a qualitative approach, examining case studies, industry trends, and technological advancements in AI integration. It critically assesses the transformations in guest interactions, operational processes, and revenue management within the sector.Findings - The integration of AI has led to enhanced guest experiences, streamlined operations, and more effective revenue management strategies. However, challenges in adoption remain, including technological barriers and concerns around data privacy. Opportunities for further growth in AI application within the industry are also highlighted.Originality/Value - This paper provides new insights into the evolving landscape of personalized hospitality, offering valuable perspectives for both industry professionals and stakeholders. It contributes to the understanding of how AI is shaping the future of hospitality services, emphasizing both its potential and the hurdles it presents.